A Highly Efficacious Electrical Biofilm Treatment System for Combating Chronic Wound Bacterial Infections. Issue 6 (20th December 2022) - Zhao, Fan; Su, Yajuan; Wang, Junying; Romanova, Svetlana; DiMaio, Dominick J.; Xie, Jingwei; Zhao, Siwei
Abstract: Biofilm infection has a high prevalence in chronic wounds and can delay wound healing. Current treatment using debridement and antibiotic administration imposes a significant burden on patients and healthcare systems. To address their limitations, a highly efficacious electrical antibiofilm treatment system is described in this paper. This system uses high‐intensity current (75 mA cm −2 ) to completely debride biofilm above the wound surface and enhance antibiotic delivery into biofilm‐infected wounds simultaneously. Combining these two effects, this system uses short treatments (≤2 h) to reduce bacterial count of methicillin‐resistant S. aureus (MRSA) biofilm‐infected ex vivo skin wounds from 10 10 to 10 5.2 colony‐forming units (CFU) g −1 . Taking advantage of the hydrogel ionic circuit design, this system enhances the in vivo safety of high‐intensity current application compared to conventional devices. The in vivo antibiofilm efficacy of the system is tested using a diabetic mouse‐based wound infection model. MRSA biofilm bacterial count decreases from 10 9.0 to 10 4.6 CFU g −1 at 1 day post‐treatment and to 10 3.3 CFU g −1 at 7 days post‐treatment, both of which are below the clinical threshold for infection. Overall, this novel technology provides a quick, safe, yet highly efficacious treatment to chronic wound biofilm infections. Abstract : A highly efficacious electrical biofilm treatment system is developed for combating chronic wound bacterial infections. This system applies 75 mA cm −2 current to completely debride biofilm above the wound surface and enhance antibiotic delivery into biofilm‐infected wounds simultaneously. As a result, this system can rapidly reduce biofilm density by 4–5 log10 scales using only 65 min treatment.